Kierunki zmian strukturalnych i proceduralnych w administracji europejskiej: [Directions of structural and procedural changes in the European administration] (Studia Prawnicze / The Legal Studies, 2023)
The subject of this article is the analysis of the basic directions of structural and procedural reforms in the European administration. Assuming, that only a well-worked out division of power may create a dynamic system, the author presents the actual conceptions of the task division between the central power and the local power. The structural changes at the central organs level are con- sidered by a prism of two problems: the adaptation of the institutional frames to the evolution in various fields of activity and the assurance of the effective coordination and control of this activity. In the field «of the territorial adminis- tration the changes are directed towards bringing the citizans closer to the centre of taking decisions, provided the principle of rationality is maintained. On the other hand, the reforms in the range of the administrative procedure lie in the „opening administration” for the citizans (gradual abolishing of traditional secrecy of the problems of general importance) new methods of management (implanting new planning, programming and budget systems).The author points out, that the complex „computarization” demands a count- erweight of the control laws, rules of systematization and preserving information about citizans. Finally, in the closing part of the article, the author presents the problem of codification of the administrative procedure, stressing that in the western countries the guiding idea of this procedure aims at the balance of two antagonistic forces: an individual and administration.